Pengaruh Harga, Lingkungan Fisik Pasar, Dan Lokasi Terhadap Loyalitas Pelanggan Di Pasar Induk Lau Cih Medan Tuntungan - Jilensiulina, Dat Ita; Sahir, Syafrida Hafni (Innovative: Journal Of Social Science Research, 2024)
This study was conducted to determine the influence of price variables, market physical environment and location on customer loyalty in the Induk Lau Cih Medan Tuntungan market. This study used an associative method analyzed with SPSS version 26. Sampling with non-probability sampling method with purposive sampling approach as many as 90 respondents. Based on the results of the study, it was obtained that the price variable had a partial and significant effect on customer loyalty in the Induk Lau Cih Medan Tuntungan market, this was obtained from the results of the thitung > ttable (4,187 > 1.987) with a Sig. value of 0.00 < 0.05. The variable of the physical environment of the market has a partial but not significant effect on customer loyalty in the Induk Lau Cih Medan Tuntungan market because the thitung > ttable (2,418 > 1.987) with a Sig. value of 0.018 > 0.05. The Location variable has a partial and significant effect on customer loyalty in the Induk Lau Cih Medan Tuntungan market because the thitung > ttabel (3,070 > 1.987) with a Sig. value of 0.003 < 0.05. For the results of the F test, it is known that the variables of price, physical environment, market and location together have a significant effect on customer loyalty because the value of Fhitung > Ftable (47,462 > 2.71) with a value of Sig. (0.000 < 0.05).